The personal experience essay in isiZulu as reflection of the writing competence of grade 12 learners - Makhanya, Winfred Nonhle Zabathembu (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.)--Stellenbosch University, 2000.